The Impact of a Counseling Techniques Course on Self-efficacy and Stigma - Allison Crowe; Richard Lamb; Janee Avent Harris; Loni Crumb; Syntia Santos Dietz (Teaching and Supervision in Counseling, 2022)
Abstract: Authors analyzed data from counseling trainees in a skills course to examine self-efficacy and stigma. It was hypothesized that self-efficacy would increase, self-stigma would decrease, and that increased self-efficacy would decrease self-stigma in CTs. Increased self-efficacy was statistically significant, but self-efficacy changes did not predict decreased self-stigma. Increased self-efficacy was predictive of self-stigma related to help-seeking. Authors offer implications for counselor educators and counselors. What is the public significance of this article? This study suggests that self-efficacy increases in counseling trainees across a clinical skills course, and that this self-efficacy also predicts the stigma trainees felt about seeking help for a mental health concern. Although it was expected that a skills course would help increase self-efficacy, the study suggests that increased self-efficacy does not relate to the stigma that trainees feel about mental health treatment.
Keywords: self-efficacy; self-stigma; help-seeking; mental illness; counselor trainees